Reference value on daily living walking parameters among Japanese adults. Issue 7 (6th May 2020) - Obuchi, Shuichi P; Kawai, Hisashi; Murakawa, Kenji
Abstract : Aim: Walking speed is closely related to numerous health outcomes. It has typically been measured in laboratory settings, where individuals can intentionally change their walking speed. It can be accurately measured in daily life using a smartphone global positioning system. We aimed to present a reference value on walking speed in daily life by sex and age. Methods: The data were obtained using a walking monitoring service involving global positioning system technology. A secondary data analysis was carried out. Four daily living walking parameters – daily living walking speed, daily living walking cycle, daily living step length and daily living cadence – of 8429 Japanese persons were measured in their daily life using a smartphone application. Results: The means (standard deviations) of daily living walking speed, daily living walking cycle, daily living step length and daily living cadence were 1.30 m/s (0.10 m/s), 1.02 s (0.06 s), 65.55 cm (5.38 cm) and 118.86 steps/min (6.76 steps/min), respectively. Notably, daily living walking speed in those aged >65 years was significantly slower than in those aged <65 years. Conclusions: The present reference values and age differences of daily living walking parameters can be used to compare daily living walking speed data measured by other devices, such as accelerometers. This could allow for a consensus on the definition of daily walking speed that can be utilized for assessing health outcomes among older individuals. Geriatr Gerontol Int 2020; 20: 664–669 .